Peningkatan Pemahaman Cara Kerja Solarcell Dan Pemanfaatan Energi Matahari Untuk Penerangan di SMKN 1 Selong Kabupaten Lombok Timur NTB - Mulyanto, Arif; Herlina Sari, Nasmi; Syahrul; Sinarep; Lalu Wahyu Alam (JURNAL KARYA PENGABDIAN, 2025)
Electricity has become an inseparable part of life's necessities along with the rapid development of technology, industry and information. The reduction in fossil energy sources and increasing awareness of preserving the environment requires us to look for alternative energy from renewable energy sources. The use of solar energy as a renewable energy source in NTB has not been widely used. This counseling was carried out at SMKN 1 Selong with the aim of introducing solar energy. Solar energy produced by solar panels is converted into electricity. Electricity is stored by the battery through a charging regulator (SCC). The battery can be used to power AC lights using an inverter. The length of use time depends on the amount of lamp power and battery power. Maintenance carried out regularly: 1. Clean the solar panels from dust or dirt. 2. Check the battery water level. Work safety is highly recommended when carrying out maintenance by turning off the MCB switch while the solar panels are being maintained.